Changes in atmospheric latent energy transport into the Arctic: Planetary versus synoptic scales - Rydsaa, Johanne Hope; Graversen, R.G.; Heiskanen, Tuomas Ilkka Henrikki; Stoll, Patrick (Quarterly Journal of the Royal Meteorological Society, 2021)
Atmospheric meridional energy transport into the Arctic plays an important role in Arctic weather and climate. The transport of latent energy in the form of water vapour strongly influences the Arctic atmosphere. The transport is achieved by circulation mechanisms on various scales and is largely comprised of extreme transport events. Here, we use a Fourier-based method of dividing the latent energy transport into spatial scales and investigate the extent to which extreme events in latent energy transport on planetary and synoptic scales have changed over the past four decades, and how they influence the Arctic winter temperatures. We find that wintertime extreme transport events on planetary scales are associated with warm temperature anomalies across the entire Arctic, while the extreme events on synoptic scales have less impact on the Arctic temperatures. We show that over the past four decades, there has been a significant increase in the wintertime latent energy transport by planetary-scale systems, and a decrease in synoptic-scale transport. This shift may have contributed to the amplified warming observed in the Arctic winter over the past decades.